PEMBENTUKAN KARAKTER KEPEMIMPINAN BERLANDASKAN NILAI-NILAI DEMOKRASI DALAM KEGIATAN EKSTRAKURIKULER PRAMUKA (Studi Deskriptif Di SMP Negeri 14 Bandung) - Lukman Hidayat, - (2020)
The character of leadership is very much needed for the younger generation as agents of change in the nation's future hopes. Needed for the younger generation as agents of changing the hopes of the nation's future. The formation of leadership character cannot be done in an instant way but must be carried out continuously and thoroughly. But behind the hard work being done there are still many problems that occur in today's young generation. A number of delinquents committed by teenagers show the fragility of the character of the younger generation. Scout extracurricular activities are very important to be implemented in schools to support the formation of character for students. This research is based on four problems, namely how the program, the process, the construction of democratic values, and the character of leadership based on democratic values formed through scout extracurricular activities. The approach used in this research is a qualitative approach using descriptive methods about scout extracurricular activities at National Senior High School 14 Bandung. Data collection is done through interviews, observation, and study documentation. The results of the study revealed that 1) the formulation of the leadership character building program was carried out through a process of deliberation involving the principals, scout coaches and students. 2) The process of character formation in scout extracurricular activities is carried out through routine training activities, achievement of SKUs, achievement of SKK, dianpinru, camps, exploration, community service, and participation activities outside of the front group in the form of competition and non-race activities. 3) The construction of democratic values is built by internalizing values through scouting methods in scout extracurricular activities. 4) The formation of leadership character in scout extracurricular activities provides a change in attitude to students so that they have characters such as justice, integrity, humility, decisiveness and openness.